Estrutura de bosque de manguezal no povoado de Quebra-Pote, na zona rural de São Luís, Maranhão - Vaz, Louise Brito (2008)
The structural characterization of mangrove vegetation, commonly called swamp, is a valuable tool regarding the ecosystem response to the existing environmental conditions, being a direct response of local conditions. Despite of full protection provided for existing laws, Brazilian mangroves in general have suffered an intense and constant degradation process, often undermines the important environmental and economic Services that they provide and, consequently, studies related to their valuation. It does not detract, however, its relevance to the government and social efforts to achieve environmental quality. This research identify the STATUS QUO of mangroves in Puzzle pot region on the ísland of Maranhao, it verifies the structural characterization of mangroves forests . The study area is located Southwest of downtown St. Louis The original physiognomy as the study area consists on three vegetation types: Secondary Forest Upland (Capoeira), Mangroves and Wetlands Forest. Secondary forest Upland is a result of the advance of human occupation and agricultural areas facilities subsistence mainly in the last three decades. This process led to the secondary vegetation, capoeira, which in combination with babassu, is today the most common vegetation type of the island. Originated from anthropogenic degradation, derived from agricultural activities based on burning method. Data collection in the field was made the same points in all campaigns (a point in Break-Pot mangrove - 2°42'07 "S; 44°12'24 "W). Trees marked the established transpectos (firm sea-land direction) were measured the height and CAP (circumference at breast height). For each of the four species that inhabit the place eleven parameters were analyzed: Total Density (DTA); Density by area (DAs); Absolute frequency (FAs); Basal area (ABs); Dominance by area (DOAS); Relative Density (DRs); Relative frequency (FRs); Relative Dominance (Dors); Importance Value (IV); Coverage (VC); Shannon-Weaver Diversity Index (H ') of community. Using the FITOPAC Program (Shepherd, 1994) for the analysis of data found. For evaluating the monitoring of leaf morphology, was collected from each species 30 sheets of sun branches, located between the fourth and sixth us five different individuais